2023
DOI: 10.2147/jir.s392482
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms Based on the Albumin/Neutrophil-to-Lymphocyte Ratio Score for Predicting Coronary Artery Disease or Subclinical Coronary Artery Disease

Abstract: Purpose To develop and validate two nomograms incorporating the albumin/neutrophil-to-lymphocyte ratio score (ANS) for predicting the risk of coronary artery disease (CAD) or subclinical CAD. Patients and Methods Four hundred fifty patients with suspected CAD who underwent coronary computed tomographic angiography were consecutively enrolled between September 2015 and June 2017. Nomograms were established based on independent predictors of CAD or subclinical CAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Based on our previous study, we used the same method to determine the cutoff points for albumin and NLR were 4.07 g/dl and 2.60, respectively [ 18 ]. Kaplan–Meier analysis both before and after PSM indicated that the ANS was a powerful prognostic factor for the clinical outcomes of ACS patients undergoing PCI (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous study, we used the same method to determine the cutoff points for albumin and NLR were 4.07 g/dl and 2.60, respectively [ 18 ]. Kaplan–Meier analysis both before and after PSM indicated that the ANS was a powerful prognostic factor for the clinical outcomes of ACS patients undergoing PCI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous research [ 19 ]. Concomitantly, the calculation methods of NLR and ANS are also the same as our previous studies [ 18 ]. The NLR was calculated using the following formula: NLR = neutrophil count (10 9 /l)/lymphocyte count (10 9 /l) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the ANS can be used as an important predictor of disease and surgery. 33 These include pancreaticoduodenectomy, 23 vascularised fibular flap reconstruction, 24 coronary artery disease, subclinical coronary artery disease, 19 neck cancer 21 and rectal cancer. 20 Based on the current research, there is no indication that the ANS is linked to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum albumin level and NLR are common biomarkers, they are easy to assess in clinical practice. However, an increasing number of studies have shown that the combination of serum albumin and NLR, as a serum albumin-NLR score (ANS), could have good prognostic value for coronary artery disease, 19 cancer 20 22 and postoperative complications. 23 24 Whether ANS could be used to measure the prognosis of COVID-19 is unclear, and this study hypothesised that ANS was a simple prognostic tool that could be used to the severity of patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%